Productivity of Boran cattle maintained by chemoprophylaxis under trypanosomiasis risk - Trail, J.C.M.; Sones, Keith R.; Jibbo, J.M.C.; Durkin, J.W.; Light, D.E.; Murray, M. (International Livestock Centre for Africa, 1985)
Evaluates the productivity of grade Boran cattle maintained by chemoprophylaxis under severe trypanosomiasis risk at Mkwaja ranch, Tanzania; uses data based on more than 20,000 calving records over the 10-year period from 1973 to 1982; discusses environmental influences on performance traits and links between tsetse population dynamics & cattle; includes comparison of Boran genotypes and its effect on pre-weaning growth characters.